The Impact of the Environment on the Development of Educational Administration - Soud, Hosni (Dirasat: Educational Sciences, 2022)
The study aims to identify the role of environment in the development of educational administration in the Ministry of Education. There is a need to build an orderly relationship between the environment and administrative development and the trend towards finding a twinning between them to reach educational reform in educational administration. This, in turn, aims to make a vital and effective contribution to the reform of the educational system. The results of the study showed that educational administration is affected by environmental changes, especially social and cultural. The development of educational administration that takes into account the social and cultural dimensions leads to qualitative improvements in the educational system. In addition, achieving qualitative leaps in the development of educational administration requires a thorough knowledge of the social structure, social relations, economic and cultural conditions. Finally, acceptance of environmental change helps in the development of educational administration..